Odpowiedzi

2010-04-12T21:02:04+02:00
A) x/3 + 1 = 5/6 +x/2 /*6
2x + 6 = 5 + 3x
2x - 3x = 5 - 6
-x = -1 /*(-1)
x = 1

b) (2x-3):4 = 1/2 + x /*4
2x - 3 = 2 + 4x
2x - 4x = 2 + 3
- 2x = 5 /: (-2)
x = - 5/2
x = -2,5

c) (x+2):9 +(x-1):3 = 1 /*9
x+2 +3x - 3 = 9
4x = 10
x = 10/4
x = 2,5

d) (2x+3):5 = (2-x):3 +x /:15
3*(2x +3) = 5*(2-x) + 15x
6x + 9 = 10 - 5x +15x
6x +5x - 15x = 10 - 9
-4x = 1 /:(-4)
x = -0,25

e) (3x-2):2 - (5x-1):10 = 0 /*10
5(3x-2) - 5x +1 = 0
15x - 10 - 5x +1 = 0
10x = 9 /:10
x = 0,9

f) x/2 = [2*(4-x)]:5 - 4 /*10
5x = 2(8 - 2x) - 40
5x = 16 - 4x - 40
9x = -24 /:9
x = -24/9
x = -2 i 6/9
x = -2 i 2/3

g) (2x -1):5 - (x-2):2 = 0,7x /*10
2(2x-1) - 5(x-2) = 7x
4x - 2 -5x + 10 = 7x
-8x = -8 /:(-8)
x = 1

h) 2x - (3x+5):4 = -1/4x - 1 /*4
8x - 3x - 5 = -1x - 4
6x = 1 /:6
x = 1/6
2 5 2
Najlepsza Odpowiedź!
2010-04-12T21:10:22+02:00
A) x/3 +1=5/6+x/2 *6
2x+6=5+3x
2x-3x=5-6
-x=-1 :-1
x=1

b)2x-3/4=1/2+x *4
2x-3=2+x
2x-x=2+3
x=5

c)x+2/9+x-1/3=1 *9
x+2+3x-3=9
4x=10 :4
x=2,5

d)2x+3/5=2-x/3+x *15
6x+9=10-5x+15x
-4X=1 :-4
x=-1/4

e)3x-5/2-5x-1/10=0 *10
15x-25-5x+1=0
10x=24 :10
x=2,4

f)x/2=2/5(4-x)-4
x/2=8/5-2x/5-4 *10
5x=16-4x-40
x=-24

g)2x-1/5-x-2/2=0,7x *10
4x-2-5x+10=7
-x=-1 :-1
x=1

h)2x-3x+5/4=-1/4x-1 *4
8x-3x-5=-x-4
6x=1 :6
x=1/6
2 5 2